2019
DOI: 10.1186/s13722-019-0166-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of extended-release naltrexone, methadone, and buprenorphine treatments following release from jail

Abstract: Background Few studies have documented patient attitudes and experiences with extended-release naltrexone (XR-NTX) opioid relapse prevention in criminal justice settings. This study assessed barriers and facilitators of jail-to-community reentry among adults with opioid use disorder (OUD) treated with XR-NTX, buprenorphine, methadone, and no medications. Methods This qualitative study conducted individual interviews with a purposeful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 31 publications
(39 reference statements)
5
38
2
Order By: Relevance
“…Participants perceived both issues as deal-breakers, but not surprisingly, they described feeling the effect of buprenorphine as particularly disappointing. Participants typically described illicit opioid use while on XR-NTX as "testing the blockade", and patients in previous studies have also reported doing this (Fishman, 2008;Jarvis, DeFulio, et al, 2018a;Kruptisky et al, 2007;Kunøe et al, 2010;Velasquez et al, 2019). Studies have previously reported subjective effects of opioids, but consensus seems to be that the "high" is not as great (as high) as it was before initiation to NTX (Jarvis, DeFulio, et al, 2018a;Kunøe et al, 2010).…”
Section: Unblocked Effects and Pharmacological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants perceived both issues as deal-breakers, but not surprisingly, they described feeling the effect of buprenorphine as particularly disappointing. Participants typically described illicit opioid use while on XR-NTX as "testing the blockade", and patients in previous studies have also reported doing this (Fishman, 2008;Jarvis, DeFulio, et al, 2018a;Kruptisky et al, 2007;Kunøe et al, 2010;Velasquez et al, 2019). Studies have previously reported subjective effects of opioids, but consensus seems to be that the "high" is not as great (as high) as it was before initiation to NTX (Jarvis, DeFulio, et al, 2018a;Kunøe et al, 2010).…”
Section: Unblocked Effects and Pharmacological Considerationsmentioning
confidence: 99%
“…Research on patients' experiences of discontinuation of XR-NTX treatment is limited. Velasquez et al (2019) assessed the perceptions of participants recently released from NYC jails, who received treatment with XR-NTX, opioid agonist treatment, or no treatment at all. Although seen as a useful post-release intervention by many, the authors found that those who discontinued XR-NTX treatment described the decision as intentional, often driven by a desire to resume opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…DOC focus group findings also suggested that re-entry to the community from jail is a high-risk and chaotic period for justice-involved individuals. It is possible that life eventssuch as finding safe housing or stable employmentmay supersede the perception of the importance of treatment and negatively impact adherence to XR-NTX post-release, which has been noted elsewhere (Velasquez et al, 2019). In addition, if an individual relapses or engages in criminal activity after release, he/ she may abscond from supervisionmaking XR-NTX administration in the community supervision office not feasible.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…The community re-entry period following release can be stressful due to housing, income, transportation, and relationship problems. Additionally, adherence to a medication regime that requires developing a relationship with a new health care provider with at least monthly clinic visits can also be challenging (Velasquez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A common barrier to initiating treatment, as reported in a population of justice-involved veterans, includes limited availability of pharmacotherapy treatment options (Finlay et al, 2016). Treatment retention is further impacted by housing insecurity, lack of financial resources, exposure to actively using friends and family, and lack of knowledge; these barriers emphasize the need for post-incarceration treatment plans that clearly specify medications for opioid use disorders (MOUD) (Velasquez et al, 2019). Another barrier is providers who are not supportive of pharmacotherapy (Harris et al, 2012).…”
Section: Introductionmentioning
confidence: 99%